The #MeToo Phenomenon on Indian Social Media: Moving Onward from the American #MeToo - Ahlawat, Ila (Asian Journal of Media and Communication, 2022)
This article sought to reflect upon the online #MeToo movement in India, as it began to unfold, especially October 2018 onwards. The focus lied upon the role of social media, mainly Twitter, in originating, sustaining and popularizing the movement both online as well as giving it a momentum in the real world, especially through mainstream news media. This article made a concerted attempt at examining technology and its interaction with gendered forms of social media communication. Through empirical and theoretical analyses, concepts such as trolling, anonymity and digital heterogeneity vis-a-vis social media feminist activism have been examined, as have been the structural shortcomings pertaining to class, caste, sexuality and race. It sought to assert that social media carried an effective potential in countering the neoliberal male discourse of selectively granting women agency and visibility in media spaces.